THE IMPACT OF IMPLEMENTING INQUIRY-BASED LEARNING ON EFL STUDENTS’ WRITTING DEVELOPMENT: A LITERATURE REVIEW - Ismiati Annur Husnaeni AR; Yustika Nur Fajriah; Pipih Setiawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Writing is considered one of the most complex skills in English as a Foreign Language (EFL) contexts as it requires both linguistic competence and higher-order thinking skills; however, many students still face difficulties due to limited vocabulary, lack of ideas, and teacher-centered instructional approaches. To address these challenges, Inquiry-Based Learning (IBL) has been proposed as an alternative approach that promotes active learning through questioning, investigation, and reflection. This study aims to synthesize previous research on the implementation of IBL in EFL writing instruction and its impact on students’ writing development. This study employed a structured narrative literature review by analyzing 29 selected articles published between 2019 and 2025 from various academic databases, including Google Scholar, ERIC, DOAJ, and SINTA-indexed journals. The findings indicate that IBL has a positive impact on students’ writing development, particularly in terms of idea generation, text organization, coherence, language accuracy, and overall writing quality. In addition, IBL enhances student engagement in the learning process and fosters critical thinking skills that support argument construction in writing. Despite these benefits, variations in research contexts and the predominance of short-term studies limit the generalizability of the findings. Therefore, Inquiry-Based Learning demonstrates strong potential as an effective instructional approach for improving writing skills in EFL contexts and is recommended for further investigation in broader contexts and over longer periods of time.